Rooting and shoot growth of six grapevine rootstocks submitted to the stratification of hardwood cuttings - DOI: 10.4025/actasciagron.v26i1.1963 - Roberto, Sérgio Ruffo (2008)
The objetive of this research was to evaluate the rooting and shoot growth characteristics of six grapevine rootstocks submitted to the stratification in water. Virus-free hardwood cuttings of the following rootstocks were used: ‘Ripária do Traviú’; ‘Kober 5BB’; ‘Campinas’ (IAC 766); ‘420-A’; ‘Schwarzmann’ and ‘Jales’ (IAC 572). Cuttings measuring 6.0 mm of width were prepared with a cut below the node in the basal portion and a cut in the internode in the superior portion, leaving 4 buds per cutting. Thus, the cuttings were submitted to the following treatments: Stratification in water during 48 hrs and No stratification in water. The cutting was performed in plastic bags containing soil growth medium, leaving 2 buds below and 2 buds above the soil surface. A randomized design with 4 replications and 10 plants per plot was used as a statistical model (2-factor arrangement). After 90 days, the following parameters were evaluated: porcentage of rooting cuttings; number of roots per cutting; and fresh and dry matter of roots. The porcentage of cuttings with shoot growth was also evaluate weekly, starting 28 days after the cutting, totalizing eight evaluations. According to the main results, it was possible to conclude that: a) the stratification of cuttings provides the highest porcentage of rooting cuttings for ‘Jales’ and the highest number of roots for ‘Kober 5BB’ and ‘Campinas’ rootstocks; b) ‘Jales’ presents the lowest number of roots per cutting; c) the fresh and dry mass, and the porcentage of cuttings with shoot growth are higher when they are submitted to the stratification treatment